1992
DOI: 10.1029/92jd00414
|View full text |Cite
|
Sign up to set email alerts
|

Absorption cross sections for gaseous ClNO2 and Cl2 at 298 K: Potential organic oxidant source in the marine troposphere

Abstract: The absorption cross sections for gaseous ClNO2 in the 200–370 nm region and for Cl2 in the 270–400 nm region have been determined at 298 K. The cross sections for Cl2 are in excellent agreement with the literature. At λ < 300 nm the absorption cross sections for ClNO2 are in good agreement with those of lilies and Takacs (1976/1977) and Nelson and Johnston (1981) but are higher than those of Martin and Gareis (1956) from 220 to 240 nm. In the tropospherically important region beyond 290 nm our results, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
5
32
0
Order By: Relevance
“…2 for ClNO 2 range from 185 to 295 nm with intensities that are weak but comparable to the less intense singlet transitions in these regions, especially at long wavelengths. Overall the calculations for ClNO 2 are consistent with the experimental spectrum, 14,16,17 but the latter lacks much structure between 225 and 450 nm but obviously has contributions from several electronic states. The triplet transitions in the BrNO 2 molecule cover wave-lengths out to nearly 380 nm and are comparable in intensity to the singlets, being an order of magnitude more intense than in ClNO 2 .…”
Section: Electronic Excitation Spectrasupporting
confidence: 72%
See 1 more Smart Citation
“…2 for ClNO 2 range from 185 to 295 nm with intensities that are weak but comparable to the less intense singlet transitions in these regions, especially at long wavelengths. Overall the calculations for ClNO 2 are consistent with the experimental spectrum, 14,16,17 but the latter lacks much structure between 225 and 450 nm but obviously has contributions from several electronic states. The triplet transitions in the BrNO 2 molecule cover wave-lengths out to nearly 380 nm and are comparable in intensity to the singlets, being an order of magnitude more intense than in ClNO 2 .…”
Section: Electronic Excitation Spectrasupporting
confidence: 72%
“…The first UV absorption spectrum was reported by Illies and Takacs. 15 Later studies by Furlan et al 14 and Ganske et al 16 also showed that absorption between 185 and 400 nm is a broad continuous band that consists of three unstructured bands. The strongest band is centered around 215 nm, a weak band around 300 nm, and a third below 185 nm which is strong.…”
Section: Introductionmentioning
confidence: 97%
“…Singh and Kasting [1988] reviewed the available data on sources of CIo from (1) oxidation of HC1 and CH3C1, (2) photolysis of chlorocarbons, (3) aerosol reactions of C1NO3, and (4) reactions of nitrogen oxides on dry NaC1 aerosol. They concluded that these processes are too slow to have much effect on the chemistry of the marine boundary layer, although recent work [e.g., Ganske et al, 1992] suggests that reactions involving nitrogen oxides may be more important than estimated by Singh and Kasting [1988]. Here we report preliminary results which indicate the presence in marine surface air of significant concentrations of inorganic chlorine gases other than HC1.…”
Section: Introductionmentioning
confidence: 55%
“…In contrast, the Cl atom production peaks at 9.9 × 10 3 molecules cm −3 s −1 (12:00), and the 24 h average Cl atom production rate was calculated to be 2.5 × 10 3 molecules cm −3 s −1 for the NC sampling regime. Other studies of Cl atom production rates in polluted and marine regions have reported a range in values from 4 × 10 3 to 4 × 10 6 molecules cm −3 s −1 for ClNO 2 and Cl 2 [ Finlayson‐Pitts , ; Ganske et al ., ]. Recently, Riedel and coauthors utilized a Master Chemical Model to model the Cl atom production from a HCl, ClNO 2 , and other Cl‐containing species in the Los Angeles outflow region and calculated a maximum Cl atom production rate of 0.5 × 10 6 atoms cm −3 s −1 at noon for the “without‐ClNO 2 ” scenario, of which HCl is the dominant source.…”
Section: Resultsmentioning
confidence: 98%